DAMPAK FATHER INVOLVEMENT TERHADAP KECERDASAN KOGNITIF DALAM MATA PELAJARAN AQIDAH AKHLAK PADA SISWA MIM 04 BLIMBING PACIRAN LAMONGAN - Mahsun; Muhammad Yunus (STAI Muhammadiyah Paciran Lamongan, 2023)
Father's participation in educating children in Indonesia is not quite satisfactory. Indonesia is the third country with low father involvement in Asia which causes various kinds of damage to children both socially and also affects children's cognitive growth as well. The party that has the biggest power in stimulating fathers to have an important role in the family, not only making a living but also participating in educating their children, is the government. Thus, we conducted research on the Impact of Father Involvement on Cognitive Intelligence in the Aqidah Akhlak Subject for MIM 04 Blimbing Paciran Lamongan Students in the 2022/2023 Academic Year. The purpose of the research is to describe the impact of father involvement on cognitive intelligence in the subject of aqidah akhlak for students of MIM 04 Blimbing Paciran Lamongan in the 2022/2023 academic year. This research is a quantitative descriptive research, whose purpose is to explain whether or not there is a relationship between one variable and another variable. From this research, the authors conclude that schools have a role to make parents aware of to invite fathers to play a more active role in the education of their children. Additionally, fathers must realize that the responsibility of educating children is not absolutely borne by mothers who already have a lot of responsibility.